2000
DOI: 10.1103/physrevb.61.13863
|View full text |Cite
|
Sign up to set email alerts
|

Exciton-polariton eigenmodes in light-coupledIn0.04Ga0.96As/

Abstract: Features of exciton-polariton eigenmodes in a series of light-coupled In 0.04 Ga 0.96 As/GaAs semiconductor multiple quantum wells with varying number of quantum wells N from 1 to 100, and with various periodicities ͑Bragg, near-Bragg, and anti-Bragg͒, are studied in linear measurements of reflection, transmission, and absorption. At Bragg periodicity ͑period dϭ x /2), a photonic band-gap mode grows in amplitude and increases linearly in linewidth with increasing N. The N times increased radiative damping rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 26 publications
(23 reference statements)
0
45
0
Order By: Relevance
“…Due to the increased absorption near excitonic transition, the transmission intensity decreases as the cavity modes approach to the exciton. And we also notice that the linewidth of transmission peaks gets broader as the cavity mode goes further away from excitonic resonance because of the increased absorption in shorter wavelength side of exciton [10]. Fig.…”
Section: Cavity Modes Coupled To Exciton In Qwmentioning
confidence: 80%
“…Due to the increased absorption near excitonic transition, the transmission intensity decreases as the cavity modes approach to the exciton. And we also notice that the linewidth of transmission peaks gets broader as the cavity mode goes further away from excitonic resonance because of the increased absorption in shorter wavelength side of exciton [10]. Fig.…”
Section: Cavity Modes Coupled To Exciton In Qwmentioning
confidence: 80%
“…Excitons in (In,Ga)As/GaAs SQW reveal tendency to a reduction of oscillator strength with decreasing well thickness [6,7], because the exciton wavefunction easily penetrates the barriers and confinementenhanced Coulomb interaction between electron and hole reduces. For both systems, the reported linewidths of heavy-hole exciton resonance are always a few times broader as compared to the radiative linewidth [7,8], which is of the order of 60 µeV [9].…”
Section: Introductionmentioning
confidence: 90%
“…We can compare our results with the data obtained by Prineas et. al. [9,19] on a set of 8.5 nm In 0.04 Ga 0.96 As/GaAs MQW Bragg structures having anti-reflection coating and studied in the normal incident geometry. The authors have demonstrated linear growth of total linewidth for increasing QW number N .…”
Section: B Reflection From Mqw Bragg Structurementioning
confidence: 99%
“…(36), (37) and (39) to derive (a, f )-representation for T . The dispersion equation following from this representation has a relatively simple form:…”
Section: Off-bragg Structuresmentioning
confidence: 99%